Living large: the experiences of large-bodied women when accessing general practice services - Russell N; Carryer J (Journal of Primary Health Care, 2013)
INTRODUCTION: Numerous studies report high levels of stigma and discrimination experienced by obese/overweight women within the health care system and society at large. Despite general practice being the most utilised point of access for health care services, there is very little international or national exploration of the experiences of large-bodied women (LBW) accessing these services. The aim of this study was to explore LBW's experiences of accessing general practice services in New Zealand. METHODS: This is a qualitative, descriptive, feminist study. Local advertising for participants resulted in eight self-identified, large-bodied women being interviewed. A post-structural feminist lens was applied to the data during thematic analysis. FINDINGS: The women in this study provided examples of verbal insults, inappropriate humour, negative body language, unmet health care needs and breaches of dignity from health care providers in general practice. Seven themes were identified: early experiences of body perception, confronting social stereotypes, contending with feminine beauty ideals, perceptions of health, pursuing health, respecting the whole person, and feeling safe to access care. CONCLUSION: Pressure for body size vigilance has, in effect, excluded the women in this study from the very locations of health that they are 'encouraged' to attend-including socialising and exercising in public, screening opportunities that require bodily exposure, and accessing first point of care health services.